CAMPUR KODE DALAM PERCAKAPAN ANTAR MAHASISWA ANGKATAN 2008 PRODI SASTRA JEPANG UNIVERSITAS BRAWIJAYA - FITRANSYAH, HERI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Sociolinguistic is a branch of linguistic science that has close relation with culture and society, interaction within speech society and reviewing about variety and various languages. Code mix is word insertion from one language into another in order to expand one’s language style.This study discussed about code mix in conversation among students of Japanese Literature of Brawijaya University, Malang. This study has the objective to found out causal factors and type of code mixing in students’ conversation.To analyze causal factor and type of code mixing, it used code mixing theory which refers to the opinion of Saville-Troike, Soewito and Basir. Method used in this study is qualitative descriptive. Data collection was done through observation, with data in the form of voice record of students talking naturally. Data analysis was conducted by listening to recording result of study object, take notes from recording result of study objects, classifying data obtained, and creating tables also collecting data which included as code mixing.Result of this study revealed that the most prominent code mixing was outer code mixing. There were 7 causal element of this code mixing which includes, (1) showing identity of a group, (2) creating relaxing situation, (3) showing prestige element, (4) for lexical needs, (5) lack of understanding in using the code, (6) for clarification, (7) talking about particular topic.